Snakin: Structure, Roles and Applications of a Plant Antimicrobial Peptide. - Oliveira-Lima, Marx; Benko-Iseppon, Ana Maria; Neto, José Ribamar Costa Ferreira; Rodríguez-Decuadro, Susana; Kido, Éderson Akio; Crovella, Sergio; Pandolfi, Valesca (Curr Protein Pept Sci, 2016)
Snakins are plant antimicrobial peptides (AMPs) of the Snakin/GASA family, formed by three distinct regions: an N-terminal signal peptide; a variable site; and the GASA domain in the C-terminal region composed by twelve conserved cysteine residues that contribute to the biochemical stability of the molecule. These peptides are known to play different roles in response to a variety of biotic (i.e. induced by bacteria, fungi and nematode pathogens) and abiotic (salinity, drought and ROS) stressors, as well as in crosstalk promoted by plant hormones, with emphasis on abscisic and salicylic acid (ABA and SA, respectively). Such properties make snakin/GASA members promising biotechnological sources for potential therapeutic and agricultural applications. However, information regarding their tertiary structure, mode of action and function are not yet completely elucidated. The present review presents aspects of snakin structure, expression, functional studies and perspectives about the potential applications for agricultural and medical purposes.